Loss estimation of a building subjected to earthquake excitions - Ho, Jolynn Hui (2014)
Earthquake is considered one of the most frequent natural disasters in the world, it occurs at unpredictable magnitudes and vibrating frequencies. The consequences of these major earthquake disasters were damaged or collapse of buildings, lives lost and time taken to rebuild what was damaged. Through the many major earthquake incidents that happened around the world (recent 7.7 earthquake magnitude incident in Balochistan province, Pakistan, killed over 900 people; A 9.0 magnitude earthquake in the north-western Pacific Ocean which led to a tsunami in Japan took more than 15,000 lives; An earthquake magnitude of 6.3 struck Christchurch, New Zealand killed over 166 people etc.), it showed that the consequences of an earthquake is disastrous and had to be dealt with. Therefore, an estimation of losses in a building caused by future uncertain earthquakes, especially those that would lead to disastrous consequences have to be determined. Estimation of losses in a building caused by future earthquakes is essential as these estimations provide detailed information to parties involved and thus able to identify areas where potential losses can be reduced and assist in recovery as well. In this report, the author is particularly interested in the evaluation of seismic loss probability distribution including its tail by evaluating the seismic loss exceedance probability. Taking into account uncertainties from structural modeling, the modeling of future uncertain excitation and the models for damage and loss analysis, the evaluation of the exceedance probability will unavoidably involve the computation of high-dimensional integrals. A new method based on stochastic simulation algorithms is proposed to compute such integrals more effectively and efficiently. The effectiveness and efficiency of the proposed method are shown by an illustrative example involving a multi- story inelastic building.